The Influence of Cafe Atmosphere and Menu Variations toward Customer Revisit Behavior (Case Study at Zoom Café & Resto Bengkalis) - Nurul Nabilah (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
Zoom Cafe & Resto is a restaurant and cafe that not only prioritizes product menu variants but has the advantage of presenting a comfortable atmosphere. This study aims to determine the partial and simultaneous effect of cafe atmosphere and menu variations on customer revisit behavior. In this study, the sample used is customers of Zoom Cafe & Resto Bengkalis as many as 100 respondents. The sampling technique used is nonprobability sampling with the type of purposive sampling technique. The analysis used includes validity and reliability tests, descriptive statistics, classic assumption tests, correlation analysis, multiple linear regression analysis, F test, t test, and the coefficient of determination. The results of the study show that cafe atmosphere has a positive effect on customer revisit behavior with value tcount>ttable is 2.152>1.984 and the significant number of 0.034<0.05. Menu variations have a positive effect on customer revisit behavior with value tcount>ttable is 10.047>1.984 and the signifcant number of 0.000<0.05. In the simultaneous test, Fcount>Ftable or 142.757>3.89 and a significant level of 0.000<0.05 with adjusted R square value of 0.741 (74,1%). Which shows that the cafe atmosphere variable and the menu variation variable simultaneously have a significant effect on customer revisit behavior at Zoom Cafe & Resto by 74.1%.